2011
DOI: 10.1016/j.devcel.2011.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Tao-1 Phosphorylates Hippo/MST Kinases to Regulate the Hippo-Salvador-Warts Tumor Suppressor Pathway

Abstract: SUMMARY Recent studies have shown that the Hippo-Salvador-Warts (HSW) pathway restrains tissue growth by phosphorylating and inactivating the oncoprotein Yorkie. How growth suppressive signals are transduced upstream of Hippo remains unclear. We show that the Sterile 20 family kinase, Tao-1, directly phosphorylates T195 in the Hippo activation loop and that, like other HSW pathway genes, Tao-1 functions to restrict cell proliferation in developing imaginal epithelia. This relationship appears to be evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
180
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(188 citation statements)
references
References 42 publications
0
180
1
1
Order By: Relevance
“…These include the Scribble (Scrib)-Discs large (Dlg)-Lethal giant larvae (Lgl) complex, atypical protein kinase C (aPKC), Crumbs (Crb) , and Echinoid (Ed) (Chen et al, 2010a;Grzeschik et al, 2010;Ling et al, 2010;Robinson et al, 2010;Yue et al, 2012), indicating a role of cell polarity and cell adhesion in Hippo pathway regulation. Furthermore, two studies identified Tao-1, a STE20 family protein kinase as a positive regulator of the Hippo pathway, possibly by directly phosphorylating and activating the Hpo kinase (Boggiano et al, 2011;Poon et al, 2011). In addition, homodimerization was also found to regulate Hpo kinase activity (Jin et al, 2012).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
“…These include the Scribble (Scrib)-Discs large (Dlg)-Lethal giant larvae (Lgl) complex, atypical protein kinase C (aPKC), Crumbs (Crb) , and Echinoid (Ed) (Chen et al, 2010a;Grzeschik et al, 2010;Ling et al, 2010;Robinson et al, 2010;Yue et al, 2012), indicating a role of cell polarity and cell adhesion in Hippo pathway regulation. Furthermore, two studies identified Tao-1, a STE20 family protein kinase as a positive regulator of the Hippo pathway, possibly by directly phosphorylating and activating the Hpo kinase (Boggiano et al, 2011;Poon et al, 2011). In addition, homodimerization was also found to regulate Hpo kinase activity (Jin et al, 2012).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
“…Mechanistically, the Hippo kinase cascade can be initiated by TAO kinases (TAOK1/2/3), which phosphorylate the activation loop of MST1/2 (Thr183 for MST1 and Thr180 for MST2; hereafter, all residues refer to human proteins) and thereby lead to MST1/2 activation (Boggiano et al 2011;Poon et al 2011). There is also evidence showing that the activation loop phosphorylation can be achieved by MST1/2 autophosphorylation (Praskova et al 2004).…”
Section: Core Components Of the Mammalian Hippo Pathwaymentioning
confidence: 99%
“…RNA interference (RNAi) lines obtained from the Bloomington Drosophila Stock Center or Vienna Drosophila Resource Center have been tested in previous studies (Das Thakur et al 2010;Genevet et al 2010;Boggiano et al 2011;Reddy and Irvine 2011;Chen and Verheyen 2012;Nagaraj et al 2012;Poernbacher et al 2012;Jukam et al 2013). slbo-Gal4-driven UAS-GFP flies were used as controls.…”
Section: Overexpression Of Hpo In Outer Border Cells Disrupts Bordermentioning
confidence: 99%